A Meta‐Analysis of the "Purchasing and Supply Management Practice–Performance Link". Issue 3 (July 2014) - Zimmermann, Friso; Foerstl, Kai
<x xml:space="preserve">Abstract</x> Resource‐based theory (RBT) suggests that purchasing and supply management (PSM) practices can help buying firms enhance their performance. Consequently, the "PSM practice–performance link" has undergone intense empirical investigation over the last two decades. Although most studies report a positive relationship between PSM practices and firm performance, it remains unclear whether and to what extent PSM practices relate to performance. We assess the empirical literature by conducting a meta‐analysis of 99 PSM studies from an RBT perspective. Our results indicate strong support for the positive relationships among PSM practices and firm performance. Our findings contribute to the literature by underlining the relevance of PSM, identifying aspects of the PSM function that can be considered "strategic" and detecting areas that require additional empirical investigation. Our research also provides guidance to managers as to which PSM practices demonstrate the strongest potential for contributing to buying firm performance.